Change in Height, Weight, and body mass index: Longitudinal data from Austria. Issue 5 (25th June 2014) - Peter, Raphael Simon; Fromm, Ella; Klenk, Jochen; Concin, Hans; Nagel, Gabriele
Abstract : Objectives: To quantify changes in height, weight and their compound effect on the body mass index (BMI) in a large cohort of Central‐European men and women. Methods: The Vorarlberg health monitoring and prevention program (VHM&PP) is a population‐based risk factor surveillance program in Vorarlberg. Data of health examinations during January 1985 to June 2005 were available including 714, 181 height and weight measurements in 185, 192 persons (53.9% women). We estimated yearly percentage change of anthropometric parameters over the age range from 20 to 85 years within intervals of 5 years. Results: We found that weight increased until the age of 70 years (from the age of 20 years: +24.8% in men and +27.6% in women), with the highest increase in men aged 20–25 years (1.07% per year). Height was shown to decrease starting from the age group 45–50 years. This decrease accelerated with age, and was more pronounced in women than in men. Conclusions: Weight is strongly related to aging. In older individuals height loss affects BMI and masks weight loss to some degree. Am. J. Hum. Biol. 26:690–696, 2014. © 2014 Wiley Periodicals, Inc.